Coordination of photosynthetic traits across soil and climate gradients. Issue 3 (16th November 2022) - Westerband, Andrea C.; Wright, Ian J.; Maire, Vincent; Paillassa, Jennifer; Prentice, Iain Colin; Atkin, Owen K.; Bloomfield, Keith J.; Cernusak, Lucas A.; Dong, Ning; Gleason, Sean M.; Guilherme Pereira, Caio; Lambers, Hans; et al.
Abstract: "Least‐cost theory" posits that C3 plants should balance rates of photosynthetic water loss and carboxylation in relation to the relative acquisition and maintenance costs of resources required for these activities. Here we investigated the dependency of photosynthetic traits on climate and soil properties using a new Australia‐wide trait dataset spanning 528 species from 67 sites. We tested the hypotheses that plants on relatively cold or dry sites, or on relatively more fertile sites, would typically operate at greater CO2 drawdown (lower ratio of leaf internal to ambient CO2, C i : C a ) during light‐saturated photosynthesis, and at higher leaf N per area (Narea ) and higher carboxylation capacity ( V cmax 25 ) for a given rate of stomatal conductance to water vapour, g sw . These results would be indicative of plants having relatively higher water costs than nutrient costs. In general, our hypotheses were supported. Soil total phosphorus (P) concentration and (more weakly) soil pH exerted positive effects on the Narea – g sw and V cmax 25 – g sw slopes, and negative effects on C i : C a . The P effect strengthened when the effect of climate was removed via partial regression. We observed similar trends with increasing soil cation exchange capacity and clay content, which affect soil nutrient availability, and found that soil properties explained similar amounts of variation in the focal traits as climate did. Although climate typically explained more trait variation than soil did, together they explained up to 52% of variation in the slope relationships and soil properties explained up to 30% of the variation in individual traits. Soils influenced photosynthetic traits as well as their coordination. In particular, the influence of soil P likely reflects the Australia's geologically ancient low‐relief landscapes with highly leached soils. Least‐cost theory provides a valuable framework for understanding trade‐offs between resource costs and use in plants, including limiting soil nutrients. Abstract : Using an Australia‐wide photosynthetic trait dataset, we tested predictions from least‐cost optimality theory, which posits that plants balance nutrient use and water loss to optimize photosynthesis. We found that leaf nitrogen and rates of water loss co‐vary with one another in response to climate and to a lesser extent, soils. While much attention has been paid to the role of climate in driving photosynthesis, fewer studies have investigated soil effects, despite the important role of soil in limiting plant growth and in shaping the distributions of vegetation communities.